(untitled) (Kronika Bydgoska, 2013)
In spite of restrictive regulations on alcohol consumption, intoxicated Bydgoszcz residents often ended up behind bars of municipal police stations. In 1923, 603 drunk people were arrested, and in 1929 - 644. 1935 was a record year, when 802 Bydgoszcz residents were arrested due to drunkenness. The cause of this state of affairs was ascribed to the too high number of bars and retails of alcoholic drinks. In the 1920s, there were 426 residents (including babies) per one establishment with alcohol, and over 80 restaurants serving alcohol operated in the city center itself. Labourers and craftsmen were the most frequent alcohol abusers, and slightly rarer - industrialists, traders and trade agents. Thus, the phenomenon was proportional to the number of individual professional groups. Bydgoszcz residents did not stand out above other urban communities as regards the amount of consumed alcohol, or reactions after alcohol abuse. Newspapers reported with tongue in cheek the adventures of strong alcoholic beverage enthusiasts. Though sometimes the humorous form had to make room for gloomy accounts of tragic endings of drunken excesses, unquestionably dominant was satire, which reduced the problem to an indispensable element of colorful urban folklore.